School-Located Influenza Vaccination Decreases Laboratory-Confirmed Influenza and Improves School Attendance - Pannaraj, Pia S. (Oxford University Press, 2014)
Background. School-located influenza vaccination (SLV) programs can efficiently immunize large numbers of school-aged children. We evaluated the impact of SLV on laboratory-confirmed influenza and absenteeism. Methods. Active surveillance for influenza-like illness (ILI) was conducted on 4455 children in 4 SLV intervention and 4 control elementary schools (grades K–6) matched for sociodemographic characteristics during the 2010–2011 influenza season in Los Angeles County, California. Combined nose/throat swabs were collected from febrile children with ILI at presentation to the school nurse or during absenteeism. Results. In SLV schools, 26.9%–46.6% of enrolled students received at least 1 dose of either inactivated or live attenuated influenza vaccine compared with 0.8%–4.3% in control schools. Polymerase chain reaction for respiratory viruses (PCR) was performed on 1021 specimens obtained from 898 children. Specimens were positive for influenza in 217 (21.3%), including 2009 H1N1 (30.9%), H3 (9.2%), and B (59.9%). Children attending SLV schools, regardless of vaccination status, were 30.8% (95% confidence interval, 10.1%–46.8%) less likely to acquire influenza compared with children at control schools. Unvaccinated children were indirectly protected in the school with nearly 50% vaccination coverage compared with control schools (influenza rate, 27.1 vs 60.0 per 1000 children; P = .023). Unvaccinated children missed more school days than vaccinated children (4.3 vs 2.8 days per 100 school days; P < .001). Conclusions. Vaccination of at least a quarter of the school population resulted in decreased influenza rates and improved school attendance. Herd immunity for unvaccinated children may occur in schools with vaccination coverage approaching 50%.